Relationships between NDVI and visual quality in turfgrasses: Effects of mowing height - Lee, Hyeonju; Bremer, Dale J.; Su, Kemin; Keeley, Steven J. (My University, 2012)
Canopy spectral reflectance may provide an objective means to evaluate visual quality of turfgrass, but evaluations of quality may be confounded by cultural practices that affect refl ectance, such as mowing height. In this 2-yr study near Manhattan, KS, we examined effects of mowing height on relationships between normalized difference vegetation index (NDVI) and visual quality ratings in Kentucky bluegrass (KBG; Poa pratensis L., ‘Apollo’) and in a KBG × Texas bluegrass (Poa arachnifera Torr.) hybrid (HBG; ‘Thermal Blue’). Mowing heights were 7.62 cm (high) and 3.81 cm (low). The NDVI averaged 4.5 to 7% greater in high-than in low-mown plots. Distinct regression models of visual quality were found at each mowing height and in each species (r2 from 0.40 to 0.81); separate relationships between NDVI and visual quality were also found between years in the same plots. Correlations between NDVI and visual quality were stronger at high than at low mowing heights, possibly because of greater green biomass at high mowing heights. The 95% confi dence intervals surrounding predictions of visual quality from NDVI ranged from ±1.34 to 2.75 (on a 1-to-9 scale). Thus, lack of precision is a concern when using these models for detection of differences between treatments. Results indicate that when using NDVI to evaluate turfgrass quality, evaluations should be limited to plots maintained at the same mowing height and with the same species to reduce variability in NDVI.
Keywords: Normalized difference vegetation index (NDVI); Turfgrass; Visual quality; Mowing height